Case Report: Endoscope-assisted single-incision double-channel mini-open hemilaminectomy for the treatment of acute thoracolumbar intervertebral disc disease in 11 dogs - Shi, Hao; Wang, Qi; Shao, Zhurui; Xu, Haojie; Yang, Yufei; Zhang, Yiwen; Ren, Ruizi; Weng, Jieen (Frontiers in Veterinary Science, 2025)
This study aims to explore the feasibility and efficacy of an endoscopic-assisted mini-open hemilaminectomy technique for spinal cord decompression in thoracolumbar intervertebral disc extrusion. A total of 11 dogs with acute thoracolumbar intervertebral disc disease were included in the study, preoperative magnetic resonance imaging (MRI) and computed tomography (CT) were used for precise localization. The surgery was performed using a lateral approach with a skin incision approximately 2 cm in length for a minimally invasive hemilaminectomy of the thoracolumbar spine. After separating the epaxial musculature below the articular process and exposing the tendon attachment of the accessory process, the endoscope and surgical instruments were placed. A nerve hook and nucleus pulposus forceps were used to remove the thoracolumbar intervertebral disc extrusions and relieve spinal cord compression. Postoperative MRI or CT confirmed complete removal of the disc extrusions with no significant complications observed, and all dogs exhibited normal gait and neurological examination results. This technique demonstrated advantages such as easy handling minimal incision, precise localization, and reduced iatrogenic damage, resulting in good postoperative recovery. This case series demonstrates that the endoscopic-assisted mini-open hemilaminectomy technique can safely be implemented to decompress the spinal cord in dogs. This novel technique adds onto the current growing surgical options for minimally invasive spinal surgery in veterinary neurosurgery.